Organ Culture Model of Aortic Valve Calcification - Chester, Adrian H.; Sarathchandra, Padmini; McCormack, Ann; Yacoub, Magdi H. (Frontiers in Cardiovascular Medicine, 2021)
A significant amount of knowledge has been gained with the use of cell-based assays to elucidate the mechanisms that mediate heart valve calcification. However, cells used in these studies lack their association with the extra-cellular matrix or the influence of other cellular components of valve leaflets. We have developed a model of calcification using intact porcine valve leaflets, that relies upon a biological stimulus to drive the formation of calcified nodules within the valve leaflets. Alizarin Red positive regions were formed in response to lipopolysaccharide and inorganic phosphate, which could be quantified when viewed under polarized light. Point analysis and elemental mapping analysis of electron microscope images confirmed the presence of nodules containing calcium and phosphorus. Immunohistochemical staining showed that the development of these calcified regions corresponded with the expression of RUNX2, osteocalcin, NF-kB and the apoptosis marker caspase 3. The formation of calcified nodules and the expression of bone markers were both inhibited by adenosine in a concentration-dependent manner, illustrating that the model is amenable to pharmacological manipulation. This organ culture model offers an increased level of tissue complexity in which to study the mechanisms that are involved in heart valve calcification.